Systematic Literature Review: The Effect Of Different Binders On Paracetamol Tablets - Nadine Ayu Syaima Gustaf Prins; Iqlima Farah Novantri; Jessica Putri Sinaga; Clarissa Zuha Swari (International Journal of Health Engineering and Technology, 2026)
This study aims to examine the effect of different binders on the physical quality of paracetamol tablets using the Systematic Literature Review (SLR) method. Paracetamol tablets are one of the preparations widely used as analgesics and antipyretics, so the choice of binder plays an important role in determining tablet quality, such as hardness, friability, disintegration time, dissolution, and physical and chemical stability. The method used is a literature study of various studies related to variations in binders in paracetamol tablet formulations and evaluation of their physical quality. The results of the study indicate that the type and concentration of binders have a significant effect on tablet characteristics. Binders such as PVP, gelatin, kawista pectin, konjac glucomannan, durian seed starch, cassava starch, pregelatinized corn starch phosphate, and various other natural starches show different effects on tablet hardness, friability, disintegration time, and dissolution. Natural binders such as pectin and modified starch show the most optimal results because they are able to produce tablets with good physical quality while maintaining optimal drug release. While synthetic binders such as PVP and gelatin provide strong binding strength and improve tablet stability, their use in high concentrations can prolong disintegration time and decrease dissolution. Overall, selecting the right binder is crucial for producing paracetamol tablets that meet pharmacopoeial requirements and provide optimal therapeutic efficacy.